Therapeutic Communication Relati Therapeutic Communication Relations, Attitudes and Nurse Performance on Patient Satisfaction in Internal Care Rooms at Lasinrang General Hospital Pinrang Regency Year 2022 - Rimahyanti Muti; Gustina (TOUR HEALTH JOURNAL, 2023)
Background: The quality of the hospital as an institution that produces health service technology products, of course, also depends on the quality of medical services and services provided to patients. Nurses are health service providers who provide 24-hour care. This also shows that the time spent by nurses to interact with patients is the most compared to other health workers. Therefore, therapeutic communication, attitudes and performance of nurses in the profession are very important in maintaining patient satisfaction. Purpose: The aim of the research is to find out the relationship between therapeutic communication and nurse performance attitudes towards patient satisfaction in the internal care room at the Lansinrang General Hospital, Pinrang Regency in 2022. Method: This type of research is a quantitative study using the correlation method, namely connecting between two variables in a situation or group of subjects using Cross-sectional approach. The sampling technique used propulsive sampling with a total of 60 respondents. Collecting data using a research questionnaire. Chi-square test analysis with a significance level of α=0.05. Results: The results of the study showed that there was a relationship between nurse therapeutic communication and patient satisfaction with ρ=0.000 < α = 0.05, there was a relationship between nurse attitudes and patient satisfaction with ρ= 0.000 <α= 0.05 and there was a relationship between nurse work and patient satisfaction with ρ=0.000 < α = 0.05. Disscusion and Conclusion : Then we can translate that there is a relationship between therapeutic communication, attitude and performance of nurses on patient satisfaction in the internal treatment room of the Lansinrang General Hospital, Pinrang Regency, in 2022.